SIMILAR RETINAL FINDINGS IN TRAUMATIC BRAIN INJURY AND ALZHEIMER’S - Cekmeceli, Selcuk N.; Kayabasi, Umur A. (International Journal of Research -GRANTHAALAYAH, 2018)
Aim: Our aim was to show similarities between retinal findings in Alzheimer’s disease (AD) and Traumatic Brain Injury (TBI). Methods: 30 patients with AD, 4 patients with TBI and 20 age-matched healthy controls were examined by FAF and SD-OCT to find amyloid plaques and tau tangles in the retina. Results: Similar images of plaques and tau tangles were detected in both diseases. Conclusion: TBI may cause neurodegeneration in the retina similar to AD.